The Effect of Advertising and Brand Image of Citilink Airlines on Consumer Buying Interest at Juanda International Airport Surabaya - Tasyana Karunia Mulia Halim; You She Melly Anne Darasta (PT FORMOSA CENDEKIA GLOBAL, 2023)
Currently, the aviation industry is experiencing rapid development. Evidenced by the many airlines that are present in providing flight services. Competition between companies looks so heated and companies are required to be able to try hard to set marketing strategies in advertising and improve the company's brand image to be able to win a competition. This study aims to determine the effect of advertising and brand image of Citilink airlines on consumer buying interest at Juanda International Airport, Surabaya. Sampling using non-probability sampling technique on purposive sampling. The research data was obtained by distributing questionnaires to 100 respondents, namely Citilink passengers who had used Citilink flight services at least once with the age criteria of 15-35 years and over. The data analysis technique used was multiple linear regression which was processed using the IBM SPSS Statistics 25 application. The results of the study show that there is a positive influence from the advertising and brand image of Citilink airlines together on consumer buying interest at Juanda International Airport, Surabaya. This is evidenced by the results of the f test obtaining a significance value of 0.000 less than 0.05 and R Square or the coefficient of determination of Advertising and Brand Image together contributing to the influence of consumer buying interest of 85.2% and the remaining 14.8% interest consumer buying is influenced by other variables not examined in this study